The Crossroad of Notary Organizations in Indonesia: Is There Any Government Guidance and Supervision? - Rahmi, Elita; Amir, Diana; Nehemia Toscany, Afrizal; Inayah, Rts. Fanny; Pratama Putra, Rifqi (Asosiasi Pengajar Hukum Tata Negara dan Hukum Administrasi Negara, 2026)
This study addresses the crossroads facing notary organizations in Indonesia and emphasizes the need for the government to anticipate this situation in order to preserve the role of notaries as public officials and holders of a noble legal profession, as well as their function as makers of authentic deeds. The study critically examines the extent of governmental decisiveness regarding the division of notary organizations, which has emerged as both a challenge and a potential opportunity, particularly in the debate between a single-bar and a multi-bar organizational model. This issue is significant given that notaries are public officials whose guidance and supervision are closely linked to the government through delegated authority exercised by the National Supervisory Council (Majelis Pengawas Notaris) and professional notary organizations. This research employs a normative juridical method, incorporating historical, conceptual, legislative, and comparative approaches, including comparisons with other professional legal organizations. The analysis is conducted through legal reasoning aimed at realizing the fundamental objectives of law, namely order, legal certainty, and societal welfare. The study finds that the division of notary organizations in Indonesia may generate both internal and external impacts. Internally, such division creates disharmony among notaries and undermines professional solidarity, thereby disrupting the effectiveness of routine supervisory mechanisms, including annual notarial examinations. Externally, organizational fragmentation risks producing deeper institutional divisions, as observed in other legal professions, which may weaken ethical enforcement mechanisms, erode adherence to the notarial code of ethics, and ultimately diminish the dignity of the notarial profession as a public office entrusted with public responsibility. This study concludes that maintaining a unified notary organization under a single-bar model is essential to safeguarding professional integrity, strengthening supervision, and enhancing the institutional credibility and public trust in the notarial profession in Indonesia.